The challenge of city competitive advantange-rethingking creative city networking (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Competition between cities in globalization has been made through various efforts. The city must also win a competition through brands in the form of quality of life of creative cities. UNESCO also lists the need for an optimal effort to develop the community's culture and creativity to stimulate the city's regeneration into sustainability.  The study aims to dissect the city of Pekalongan as a case study. The research uses qualitative methods with data collection through the Big Data harvesting process analyzed through the interpretation process. The findings are the relationship between the physical elements of city space and the strong meaning concerning the creative abilities possessed by its people, both tangible and intangible. It is this strength that underlies the distinctive and sustainable cultural development to build a city competitive advantage.
Keywords: City branding; Vity competitive advantage; Pekalongan; Place attachment